Genetic Profile of Adenomatoid Odontogenic Tumor and Ameloblastoma. A Systematic Review - Marín, Constanza; Niklander, Sven E.; Martínez-Flores, René (Frontiers in Oral Health, 2021)
Purpose: to perform a comprehensive and systematic critical appraisal of the genetic alterations reported to be present in adenomatoid odontogenic tumor (AOT) compared to ameloblastoma (AM), to aid in the understanding in their development and different behavior. Methods: an electronic search was conducted in PubMed, Scopus and Web of Science during March 2021. Eligibility criteria included publications on humans which included genetic analysis of AOT or AM. Results: a total of 43 articles reporting 59 AOTs and 680 AMs were included. Different genomic techniques were used, including whole-exome sequencing, direct sequencing, targeted next-generation sequencing panels and TaqMan allele-specific qPCR. Somatic mutations affecting KRAS were identified in 75.9% of all AOTs, mainly G12V; whereas a 71% of the AMs harboured BRAF mutations, mainly V600E. Conclusions: The available genetic data reports that AOTs and AM harbour somatic mutations in well-known oncogenes, being KRAS G12V/R and BRAFV600E mutations the most common respectively. The relatively high frequency of ameloblastoma compared to other odontogenic tumors, such as AOT, has facilitated the performance of different sequencing techniques, allowing the discovery of different mutational signatures. On the contrary, the low frequency of AOTs is an important limitation for this. The number of studies that have a assessed the genetic landscape of AOT is still very limited, not providing enough evidence to draw a conclusion regarding the relationship between the genomic alterations and its clinical behaviour. Thus, the presence of other mutational signatures with clinical impact, co-occurring with background KRAS mutations or in wild-type KRAS cases, cannot be ruled out. Since BRAF and RAS are in the same MAPK pathway, it is interesting that ameloblastomas, frequently associated with BRAFV600E mutation have aggressive clinical behavior, but in contrast, AOTs, frequently associated with RAS mutations have indolent behavior. Functional studies might be required to solve this question.